The role of corporate governance mechanisms in the emerging economies - Younas, Afshan; Veerasamy, Rengarajan; Wahaibi, Mahmood Al; Subramanian, Kabaly P; Elzahar, Hany (Edelweiss Applied Science and Technology, 2025)
Corporate governance has attracted extensive attention globally due to its overarching impact on a business’s future prospects. More specifically, the progression of social and environmental challenges requires businesses to respond to and address stakeholders’ concerns worldwide. Corporate governance practices are integral to the evolution and management of businesses, particularly in emerging nations. This study aims to investigate and understand the concept of corporate governance, examining its definition, importance, theories, and codes. Corporate governance mechanisms ensure that firms are operated transparently, responsibly, and ethically, which is essential for sustainable development. Theories of corporate governance are significant as they provide insights into the roles and interests of various stakeholders. The study also highlights some of the most important codes of corporate governance that establish frameworks and guidelines for the accountable management and control of companies. These codes are designed to facilitate efficient, ethical, and transparent business administration, ultimately benefiting stakeholders.